2004
DOI: 10.1007/s00122-004-1782-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel inter-series hybrids in Solanum, section Petota

Abstract: Sexual hybrids between distantly related Solanum species can undergo endosperm failure, a post-zygotic barrier in inter-species hybridizations. This barrier is explained by the endosperm balance number (EBN) hypothesis, which states that parents must have corresponding EBNs for viable seed formation. Tests for inter-crossability were made involving the Mexican species Solanum pinnatisectum Dunal. (series Pinnatisecta, ApiApi, 1EBN), autotetraploids of this species, Solanum verrucosum Schlechtd. (series Tuberos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 62 publications
1
32
0
5
Order By: Relevance
“…But the percentage of successfully rescued ovules was very low indeed. This rather low proportion could perhaps be improved by the imposition of a variety of physical and/or chemical treatments, for example, bud pollination (Trindade et al 2001), in vitro pollination (Van Tuyl et al 1991) and phytohormone treatment (Dinu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…But the percentage of successfully rescued ovules was very low indeed. This rather low proportion could perhaps be improved by the imposition of a variety of physical and/or chemical treatments, for example, bud pollination (Trindade et al 2001), in vitro pollination (Van Tuyl et al 1991) and phytohormone treatment (Dinu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance in the ploidy level of the endosperm and embryo or in the ratio of maternal and paternal nuclei making up the endosperm can affect successful seed formation and germination (Dinu et al 2005;Recupero et al 2005), although this usually results in complete endosperm failure and death of the embryo. Harvey & Braggins' (1985) study of one population found that fertilisation is not involved in the production of the endosperm in P. hamiltonii, which may be derived from one or both of the polar nuclei and is triploid, the same chromosome number as the embryo and parent plant.…”
Section: Differences Between Speciesmentioning
confidence: 99%
“…pinnatisectum and S. cardiophyllum are primitive 2x species from Mexico and the southwest United States that are reproductively isolated from 4x cultivated potato and their 2x haploids (Novy and Hanneman 1991;Kuhl et al 2002;Ramon and Hanneman 2002;Dinu et al 2005). Several approaches for direct introgression into cultivated potato have been used to overcome reproductive barriers between potato species.…”
Section: Introductionmentioning
confidence: 99%